2011
DOI: 10.1001/jama.2011.1169
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Tolerability of Pegloticase for the Treatment of Chronic Gout in Patients Refractory to Conventional Treatment

Abstract: clinicaltrials.gov Identifier: NCT00325195.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
293
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 438 publications
(305 citation statements)
references
References 33 publications
11
293
0
1
Order By: Relevance
“…The clinical benefits and risks of these very low serum urate levels are currently uncertain. Although both clinical trial data and observational studies have shown benefit in flare reduction and tophus regression with very low serum urate concentrations 16, 23, the European League Against Rheumatism has recommended against lowering UA to these levels for more than several years 2.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical benefits and risks of these very low serum urate levels are currently uncertain. Although both clinical trial data and observational studies have shown benefit in flare reduction and tophus regression with very low serum urate concentrations 16, 23, the European League Against Rheumatism has recommended against lowering UA to these levels for more than several years 2.…”
Section: Discussionmentioning
confidence: 99%
“…Other qualitative and quantitative studies have covered an even wider range of gout-related issues including treatment, knowledge, disease monitoring, outcomes and patient and clinician perspective within each study [24,25,42]. The emergence of clinical trial and survey data showing QOL deficits in gout patients [18-23] indicates that we need a better understanding of the patient perspective of the impact of gout on their lives.…”
Section: Discussionmentioning
confidence: 99%
“…Gout has a significant negative effect on patient’s quality of life (QOL) [18-21] and effective treatment improves QOL [22,23]. Therefore, it is critical to understand the specific impact of gout on patients’ lives.…”
Section: Introductionmentioning
confidence: 99%
“…Each uricase monomer has been conjugated with 10 ± 1 strands of 10-kDa monomethoxy-PEG (mPEG) to reduce its immunogenicity. [36] However, anti-PEG Abs have been detected since the early phase 1 trial: a single subcutaneous (SC) injection of pegloticase induced the generation of both anti-PEG IgM and IgG Abs in 5 out of 13 patients (38%). [37] These antibodies were associated with the quick drug clearance and three anti-PEG positive subjects had injection-site reactions at 8–9 days post-injection.…”
Section: Anti-peg Abs In the Clinicmentioning
confidence: 99%
“…Several subsequent trials also found high incidence rates of anti-drug antibodies (ADAs), but their specificity was not determined. [36, 39]…”
Section: Anti-peg Abs In the Clinicmentioning
confidence: 99%